The Lack of Technology Policy. The State of the Art in Croatia. - Lažnjak, Jasminka (2001)
The paper analizes the lack of technology policy in Croatia in past ten years of transition. Social causes and consequences of such "policy" are disscussed manly using social constructivist approach in study of society&technology relationship. The fact of nonexisting strategy of technological development in Croatia is treated as failure of policy. The harm that was done by this way is presented by thesis of technological lag which is very difficult to overcome.
Projekt MZOS
ENG